Kebijakan Pengadaan dalam Pengendalian Susu Segar pada Koperasi Peternak Bandung Selatan Pangalengan - Kiki Lesmana; Heri Nugraha; Ati Atul Quddus (J-Coop : Journal of Co-operative, 2026)
The South Bandung Livestock Cooperative (KPBS) Pangalengan operated an upstream-to-downstream milk procurement system that involved farmers, Milk Collection Points (MCPs), and Dairy Processing Industries (IPS), within which a set of policies was enforced to control the quantity and quality of fresh milk. This study aimed to analyze the procurement policy applied in controlling fresh milk at KPBS Pangalengan using a mixed-method approach supported by a forecasting method to predict future milk reception and delivery. Data were collected through direct observation, interviews with key informants at the production unit, documentation, and secondary data on milk reception and delivery. The results showed that the milk procurement system had been implemented in an integrated manner, covering milking based on Good Manufacturing Practices (GMP), collection at the MCP, digital barcode-based quality testing, and direct distribution to industrial partners without long-term storage. KPBS applied a quality-based incentive and penalty scheme, technical training, and facility support for farmers. Milk was distributed proportionally to several industrial partners, with PT. Ultra Jaya as the largest recipient. Milk production was strongly influenced by weather and humidity conditions that could trigger heat stress in dairy cattle, thereby reducing both the quantity and quality of milk. Forecasting using the Exponential Triple Smoothing (ETS) method indicated a stable and slightly increasing short-term trend in milk reception and delivery, with a good to very good level of forecasting accuracy (MAPE of 6.05% and 13.57%, respectively). The study concluded that procurement policies supported by a technology-based climate information system and forecasting methods strengthened production resilience, increased member participation, and aligned with cooperative principles oriented toward member welfare.